Moving on? Neoliberal continuities through crisis: the case of the Chilean salmon industry and the ISA virus. (December 2015) - Bustos, Beatriz
Recent development literature on Latin America has discussed whether a 'postneoliberal' era has arrived. In this paper I argue that determining the arrival of a postneoliberal moment requires an examination of how capital crises are resolved by the state and the market to see whether institutions and the policy responses created by their interaction constitute a new approach to capital accumulation. After presenting geographical debates on crisis formation, I focus on the Infectious Salmon Anemia crisis that affected the Chilean salmon industry in 2008, and which raised questions about Chile's neoliberal success and global integration. Using interviews, press reports, and public data, I find that the policy responses that were implemented—namely, a new regulatory framework, increased state oversight, and geographical relocation—deepened Chile's trust in a neoliberal economy. This finding suggests that, at least in terms of environmental governance, we have not arrived at a postneoliberal moment.